The Gig Economy Revolution in Nepal: Analyzing Challenges and Opportunities for Digital Governance - Bhul, Baburam (Prashasan: The Nepalese Journal of Public Administration, 2025)
This study analyzes the rapid expansion of the gig economy in Nepal, which began in the early 2000s and has accelerated significantly due to technological advancements, increasing e-commerce, evolving consumer habits (the "new normal"), and the impacts of the COVID-19 pandemic. Through an interpretive review, this research explores the challenges and opportunities within Nepal's gig economy, focusing on current legal frameworks, the absence of social protections, and its broader economic effects. The findings highlight significant gaps in legal protections for gig workers, complex tax issues, and persistent consumer trust problems. The analysis reveals that gig work contributes approximately 6% to Nepal's GDP, with over 25% of gig workers originating from rural areas, indicating a major shift in employment dynamics. The study identifies various challenges and opportunities for government agencies to establish a more equitable and sustainable gig economy, offering practical policy recommendations for a changing labor market.